Strategi Optimalisasi Peran Wali Murid untuk Meningkatkan Minat Belajar Siswa di Masa Pandemi - Yaqin, Muhammad Ainul; Romli, Mustain; Ilyas, Zainul (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2021)
In the era of COVID-19 pandemic, teaching and learning process which was taught face-to-face, now has to switch to work from home (online). It makes students in each institution experience changes and have to get used to the nuances of different learning process. It raises its own problems that result in disrupted learning. It makes students feel bored and has an impact on decreasing learning interest. This research is intended to examine the problems that occur in learning process during the pandemic era in a comprehensive and straightforward manner by optimizing the process of education through the role of parents to increase student interest in learning. This research uses a descriptive qualitative method that focuses on describing all problems as well as finding solutions. The instruments used in data collections are interview and observation. Based on the results and discussion in the study, it was found that there were several obstacles experienced by institutions and parents in overseeing online learning, such as limitations in accessing the internet due to the lack of data and not having a cell phone. In addition, it was also found that the roles and efforts of parents is very essensial, such as providing mentoring or guidance one after another, and reviewing the learning outcomes from teachers after online learning. So that both of them complement each other through the efforts that are applied. That way, learning remains in a good position and students can still learn well and can grow their learning interest.